Waqf dimensions in the context of improving the mosque prosperity board's economy based on law number 41 of 2004 regarding waqf - Jumadiah Jumadiah; Faisal Faisal; H Hamdani; S Sutriani (Jurnal Geuthèë: Penelitian Multidisiplin, 2023)
Waqf is a legal act of a person or group of people or legal entity which separates part of their property for the benefit of worship or other public purposes in accordance with Islamic teachings” and “Waqf objects are all objects, whether movable or immovable, which have durability that is not disposable and valuable according to Islamic teachings and as a support for the development of Islamic society. Law Number 41 of 2004 concerning waqf contains a variety of formal rules which form the basis for the development of productive waqf in Indonesia. In addition, a body has also been established which is the aegis of all institutions in the country. Islam does not only regulate prayer, fasting and pilgrimage but also includes mu'amalah, therefore how are efforts to increase the economy of the Mosque Prosperity Agency (BKM). The mosque is a center for worship facilities for people in increasing ubudiyah to Allah SWT, waqf assets have positive economic potential for the welfare of the community. In Indonesia, it is hoped that waqf will develop in its management so that it can empower the economy of people in need. This study aims to determine the dimension of waqf in improving the economy of the people in Indonesia. The research methodology used is literature review. The reference source for this research is previous research on productive waqf.